2020
DOI: 10.1038/s41598-020-58819-5
|View full text |Cite
|
Sign up to set email alerts
|

Validating a targeted next-generation sequencing assay and profiling somatic variants in Chinese non-small cell lung cancer patients

Abstract: Non-small cell lung cancer (NSCLC) is featured with complex genomic alterations. Molecular profiling of large cohort of NSCLC patients is thus a prerequisite for precision medicine. We first validated the detection performance of a next-generation sequencing (NGS) cancer hotspot panel, OncoAim, on formalin-fixed paraffin-embedded (FFPE) samples. We then utilized OncoAim to delineate the genomic aberrations in Chinese NSCLC patients. Overall detection performance was powerful for mutations with allele frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 55 publications
(62 reference statements)
8
19
1
Order By: Relevance
“…Although the mutational frequencies of KRAS and TP53 were also higher in smoking than those in nonsmoking patients in this study, the statistical analysis showed no significant difference (17.1% vs. 7.3%, P = 0.052; and 62.9% vs. 52.7%, P = 0.22, respectively). In contrast to previous studies 43 , 44 , our results revealed a series of smoking-associated genes, including CDKN2A , CCND1 , SMARCA4 , CCNE1 , STK11 , KEAP1 , KMT2C , FAT1 , FGFR1 , and NFE2L2 . This discrepancy may be caused by regional differences among populations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although the mutational frequencies of KRAS and TP53 were also higher in smoking than those in nonsmoking patients in this study, the statistical analysis showed no significant difference (17.1% vs. 7.3%, P = 0.052; and 62.9% vs. 52.7%, P = 0.22, respectively). In contrast to previous studies 43 , 44 , our results revealed a series of smoking-associated genes, including CDKN2A , CCND1 , SMARCA4 , CCNE1 , STK11 , KEAP1 , KMT2C , FAT1 , FGFR1 , and NFE2L2 . This discrepancy may be caused by regional differences among populations.…”
Section: Discussioncontrasting
confidence: 99%
“…Sacher et al focused on the GAs of young lung cancer patients and identified that mutations in EGFR , ALK , and ERBB2 trend to occur in younger NSCLC patients 42 . According to different age groups, Jiang et al reported that mutations in EGFR and TP53 were associated with age in Chinese NSCLC patients 43 . In contrast to this study, we did not detect an association between age and TP53 and EGFR mutations.…”
Section: Discussionmentioning
confidence: 99%
“…For NRF2 activation, it is important to consider that other mutated genes that contribute to NSCLC development (EGFR, TP53, KRAS, PTEN and PIK3CA) [135,148] correlate with particular NFE2L2/KEAP1 mutations. Mutations in NFE2L2 usually co-occur with PI3KCA and TP53 mutations [149,150]; meanwhile, KEAP1 mutations co-occur more frequently with mutations in K-RAS or STK11 [105,138].…”
Section: Somatic Mutations Of Nfe2l2/keap1/cul3mentioning
confidence: 99%
“…Mutations in NFE2L2 usually co-occur with PI3KCA and TP53 mutations [149,150]; meanwhile, KEAP1 mutations co-occur more frequently with mutations in K-RAS or STK11 [105,138]. EGFR mutations can coexist with NFE2L2 mutations [148,151].…”
Section: Somatic Mutations Of Nfe2l2/keap1/cul3mentioning
confidence: 99%
“…According to various studies, multigene testing for nonsynonymous mutations, translocations and copy number variations of a variety of genes is recommended to identify optimal treatment options for patients with advanced tumors, including NSCLC [ 21 , 22 , 23 ]. Next-generation sequencing (NGS), which does not reveal genetic aberrations of only one but multiple genes at the same time, represents a tissue-sparing alternative for the detection of various genetic aberrations.…”
Section: Introductionmentioning
confidence: 99%